2001
DOI: 10.1021/jp011780g
|View full text |Cite
|
Sign up to set email alerts
|

The Decomposition Pathways of Methanol on Clean Ru(0001), Studied by Reflection−Absorption Infrared Spectroscopy (RAIRS)

Abstract: The adsorption and decomposition of methanol on clean Ru(0001) were investigated by reflection−absorption infrared spectroscopy (RAIRS). At low temperature (90 K) and coverage (0.1 L), it was confirmed that methanol adsorbs dissociatively as methoxide (CH3O−). No experimental evidence was obtained of an alternative decomposition for high coverage. Different bonding sites and geometries, depending on temperature and coverage, were proposed for methoxide and correlated with the corresponding CO stretching wavenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
76
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(88 citation statements)
references
References 50 publications
11
76
1
Order By: Relevance
“…In this subsection, we analyze relevant experimental published results in Ru catalysts regarding DMFC or methanol electrooxidation context [44,45]. They explore several aspects of the reaction and catalyst role, in particular those relating with thermal evolution.…”
Section: Experimental Results Ii: Ru Catalystsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this subsection, we analyze relevant experimental published results in Ru catalysts regarding DMFC or methanol electrooxidation context [44,45]. They explore several aspects of the reaction and catalyst role, in particular those relating with thermal evolution.…”
Section: Experimental Results Ii: Ru Catalystsmentioning
confidence: 99%
“…Barros et al experiments discriminate temperature effects per surface exposure. At 90 K (considered a low temperature), experimental data indicate a fast dehydrogenation of methanol to methoxide (CH 3 O) in the solo low coverage crystal Ru(0001) surface, while at the same temperature and catalyst metal surface, a high coverage presented no evidence of detection of scission of the C-O bond [44]. Gadzincki et al found isolated methanol molecules in solo Ru(0001) surfaces, when both temperature (≈80 K) and coverage was low [45].…”
Section: Experimental Results Ii: Ru Catalystsmentioning
confidence: 99%
See 3 more Smart Citations